Regulation of Exocyst Function by the Small GTPase RalA. - Hatch, Harold. (2017)
Abstract: The exocyst is a multisubunit complex that is required for the vesicular trafficking of many proteins. Regulation of exocyst assembly occurs in part through multiple small GTPases, including RalA. Previous work in our lab has shown RalA to be essential for two exocyst dependent processes, delivery of E-Cadherin to the basolateral membrane of H-Ras transformed keratinocytes, and the secretion of HGF from primary fibroblasts. Some, but not all, exocyst subunits may be required for specific processes. We have identified Sec8 as an important regulator of E-Cadherin delivery. Depletion of Sec8 from keratinocytes grown in organotypic models of squamous cell carcinoma resulted in decreased ECadherin levels and increased invasion of the keratinocytes into the underlying dermis. These results phenocopied depletion of RalA implying that Sec8 is downstream of RalA. In order to gain further insight into the mechanism by which RalA and Sec8 regulate E-Cadherin delivery we isolated the exocyst complex from control and RalA depleted tissues by Sec8 immunoprecipitation of the epithelial layer and analyzed samples by 2D-DIGE. Similar experiments were conducted in fibroblasts to examine the role of RalA and Sec8 in HGF secretion. While 2D-DIGE failed to identify changes in proteins associated with Sec8 which may regulate vesicular trafficking of E-Cadherin in keratinocytes, we were able to identify RPLP1 as a potential Sec8 interacting protein in fibroblasts. Further work is required to validate the specificity of this interaction and its contribution to HGF secretion.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Biochemistry.; Advisors: Larry Feig, and Gail Sonenshein.; Committee: Brian Schaffhausen, and Alexei Degterev.; Keyword: Biochemistry.